Phase II study of concomitant radiotherapy with atezolizumab in oligometastatic soft tissue sarcomas: STEREOSARC trial protocol - Nicolas Penel; Dominique Vaur; Juliette Thariat; Alexandre Escande; Jennifer le Guevelou; Colin Debaigt; Esma Saada-Bouzid; Julien Viotti; Nazim Khalladi; David Thibouw; Marie Pierre Sunyach; Laurence Moureau-Zabotto; et al. (BMJ Open, 2020)
Introduction Up to 50% of soft tissue sarcoma (STS) patients develop metastases in the course of their disease. Cytotoxic therapy is a standard treatment in this setting but yields average tumour response rates of 25% at first line and ≤10% at later lines. In oligometastatic stage, stereotactic body radiation therapy (SBRT) allows reaching high control rates at treated sites (≥80%) and is potentially equally effective to surgery in term of overall survival. In order to shift the balance towards antitumour immunity by multisite irradiation, radiation could be combined with inhibitors of the immunosuppressive pathways.Methods and analysis STEREOSARC is a prospective, multicentric, randomised phase II, designed to evaluate the efficacy of SBRT associated with immunotherapy versus SBRT only. Randomisation is performed with a 2:1 ratio within two arms. The primary objective is to evaluate the efficacy, in term of progression-free survival (PFS) rate at 6 months, of immunomodulated stereotactic multisite irradiation in oligometastatic sarcoma patients. The secondary objectives include PFS by immune response criteria, overall survival, quality-of-life evaluation and developing mathematical models of tumour growth and dissemination predictive of oligometastatic versus polymetastatic evolution. Patients will be randomised in two groups: SBRT with atezolizumab and SBRT alone. The total number of included patients should be 103.Trial registration The trial is registered on ClinicalTrials.gov (ID: NCT03548428).Ethics and dissemination This study has been approved by Comité de Protection des Personnes du sud-ouest et outre-mer 4 on 18 October 2019 (Reference CPP2019-09-076-PP) and from National Agency for Medical and Health products Safety (Reference: MEDAECNAT-2019-08-00004_2017-004239-35) on 18 September 2019.The results will be disseminated to patients upon individual request or through media release from scientific meetings. The results will be communicated through scientific meetings and publications.